Species and population level molecular profiling reveals cryptic recombination and emergent asymmetry in the dimorphic mating locus of C. reinhardtii - De Hoff, Peter L.; Ferris, Patrick; Olson, Bradley J.; Miyagi, Ayano; Geng, Sa; Umen, James G. (My University, 2013)
Heteromorphic sex-determining regions or mating-type loci can contain large regions of non-recombining sequence where selection operates under different constraints than in freely recombining autosomal regions. Detailed studies of these non-recombining regions can provide insights into how genes are gained and lost, and how genetic isolation is maintained between mating haplotypes or sex chromosomes. The Chlamydomonas reinhardtii mating-type locus (MT) is a complex polygenic region characterized by sequence rearrangements and suppressed recombination between its two haplotypes, MT+ and MT−. We used new sequence information to redefine the genetic contents of MT and found repeated translocations from autosomes as well as sexually controlled expression patterns for several newly identified genes. We examined sequence diversity of MT genes from wild isolates of C. reinhardtii to investigate the impacts of recombination suppression. Our population data revealed two previously unreported types of genetic exchange in Chlamydomonas MT—gene conversion in the rearranged domains, and crossover exchanges in flanking domains—both of which contribute to maintenance of genetic homogeneity between haplotypes. To investigate the cause of blocked recombination in MT we assessed recombination rates in crosses where the parents were homozygous at MT. While normal recombination was restored in MT+×MT+ crosses, it was still suppressed in MT−×MT− crosses. These data revealed an underlying asymmetry in the two MT haplotypes and suggest that sequence rearrangements are insufficient to fully account for recombination suppression. Together our findings reveal new evolutionary dynamics for mating loci and have implications for the evolution of heteromorphic sex chromosomes and other non-recombining genomic regions.
Keywords: Mating-type loci; Genetic isolation; Chlamydomonas reinhardtii; Recombination